Prevalence and Characteristics of Campylobacter Throughout the Slaughter Process of Different Broiler Batches - Zhang, Xiaoyan; Tang, Mengjun; Zhou, Qian; Zhang, Jing; Yang, Xingxing; Gao, Yushi (Frontiers in Microbiology, 2018)
Handling and consumption of chicken meat are risk factors for human campylobacteriosis. This study was performed to describe the Campylobacter population in broiler carcasses and environmental samples throughout the slaughter process. Moreover, the genetic diversity and antimicrobial resistance of the Campylobacter strains were evaluated. Cloacal swabs, samples from carcasses at different stages, and environmental samples were collected thrice from the different flocks at the same abattoir located in Central Jiangsu, China. Campylobacter isolated from the three batches (n = 348) were identified as Campylobacter jejuni (n = 117) and Campylobacter coli (n = 151) by multiplex PCR. Characterization by multilocus sequence typing revealed a specific genotype of Campylobacter for each batch. Antimicrobial sensitivity to 18 antibiotics were analyzed for all selected strains according to the agar diffusion method recommended by the Clinical and Laboratory Standards Institute. Antibiotic susceptibility tests indicated that the majority of the tested isolates were resistant to quinolones (>89.7%). Less resistance to macrolide (59.8%), gentamicin (42.7%), amikacin (36.8%) was observed. Results showed that 94.0% of the tested strains demonstrated multidrug resistance.